Work Environment as a Moderation of the Effect of Job Satisfaction and Organizational Commitment on the Performance of Sleman District Social Service Employees - Fauziah, Arina; Kirana, Kusuma Chandra; Septyarini, Epsilandri (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
The purpose of this study was to determine the effect of job satisfaction and commitment on employee performance as well as the influence of the work environment in memorizing the relationship between job satisfaction and commitment to the performance of the Dinas Sosial Kabupaten Sleman employee. The population and samples used in this study were all employees of the Dinas Sosial Kabupaten Sleman, totaling 60 people using the saturated sample method.. Methods of data collection using questionnaires. Partial Least Square (PLS) with the help of the SmartPLS 3.3.7 application was used as data analysis through three testing stages, namely: evaluation of the measurement model (outer model), evaluation of the structural model (inner model) and hypothesis testing. The results showed that there was a positive and significant effect of job satisfaction and organizational commitment variables on employees performance. The work environment cannot moderate the relationship between job satisfaction and employee performance and the work environment can moderate the relationship between organizational commitment to employee performance of the Dinas Sosial Kabupaten Sleman.